Analysis of parent support in career planning of vocational students - Putra, Febri Wandha; Yusuf, A Muri; Solfema, Solfema (Universitas Negeri Padang, 2019)
Career planning is the first step of students in achieving success. One factor that plays a role in career planning is parental support.The purpose of this study was to explore parents suport in vocational student career planning.The data were statistically analyzed using the Rasch model statistical fit analysis. The present study examined 112 vocational students. The results showed that parental support played an important role in student career planning. The results highlight the positive role that parents can play in students’ vocational career planning by supporting their with emotional, esteem, instrumental and information can helping them make a good career planning.